2023
DOI: 10.3390/ijms24129863
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anticancer Activity of A-Ring-Modified Derivatives of Dihydrobetulin

Abstract: Multidrug resistance (MDR) is a common phenomenon in clinical oncology, whereby cancer cells become resistant to chemotherapeutic drugs. A common MDR mechanism is the overexpression of ATP-binding cassette efflux transporters in cancer cells, with P-glycoprotein (P-gp) being one of them. New 3,4-seco-lupane triterpenoids, and the products of their intramolecular cyclization with the removed 4,4-gem-dimethyl group, were synthesized by the selective transformations of the A-ring of dihydrobetulin. Among the semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Although TQ has shown great potency, its clinical trials was suspended recently due to obvious side effects reported in the phase III clinical trial of lung cancer. 28 Therefore, lots of P-gp inhibitors 29–70 with new scaffolds are continuously being developed to enhance activity and selectivity. However, in order to truly obtain clinically applicable sensitizers for resistant tumors, the exploration in this field is still ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…Although TQ has shown great potency, its clinical trials was suspended recently due to obvious side effects reported in the phase III clinical trial of lung cancer. 28 Therefore, lots of P-gp inhibitors 29–70 with new scaffolds are continuously being developed to enhance activity and selectivity. However, in order to truly obtain clinically applicable sensitizers for resistant tumors, the exploration in this field is still ongoing.…”
Section: Introductionmentioning
confidence: 99%